“Students’ attitudes and motivation towards english learning” - Espín Vásquez, Indira Jhuliané (2023)
Nowadays, so many people, especially the youngest English learners, must have a positive attitude to achieve personal or academic results. In addition, motivation and attitude are fundamental components to learn English since it stimulates effort and commitment to the students’ objectives. The main goal of this quantitative-deductive research is to describe the attitudes and motivation towards English learning that present fifth, sixth and seventh grade students at “Jean Piaget” Educational Unit The applied instruments were surveys made by Asmali (2017) in which the internal consistencies of the scales were a= .85 and a= .87 scales respectively. Furthermore, a validation of the translation of the instrument into Spanish was carried out, approved by 3 professors from the Technical University of Cotopaxi. The participants in this study were 78 middle school students from Unidad Educativa Jean Piaget, that is, students of fifth, sixth and seventh grade. Subsequently, the data was collected and analyzed using EXCEL. The results showed that most students have a high level of motivation in learning the English language. Finally, these results will allow English teachers to know the high level of motivation and attitude that students have and thus be able to equip them to prosper in an interconnected world. In addition, it is recommended to encourage future research in this field to adapt and improve language teaching strategies in response to the changing needs and aspirations of students.